Powers in conflict: changes and disputes on menphite priesthood of Ptah in Roman Egypt - Pinto, Renato; Braga Gurgel, Victor (Romanitas - Revista de Estudos Grecolatinos, 2025)
In this study, we will address the main narratives about the changes that occurred in the high priesthood of Ptah from Memphis, in the Early Roman Period. The enigmatic death of the young Memphite high priest Imhotep/Padibastet IV, the last of his lineage, two days before Augustus’s entry into Alexandria, is commonly interpreted as a deed of the latter, even though recently this view has been challenged, attributing its responsibility to quarrels internal to the family of Memphite pontiffs themselves. Firstly, we will seek to understand the strategies employed by Rome, in general, and by Octavian in particular, in the search for the suppression/control/reduction of the political-social-economic prestige of the clergy. Soon after, we will show the likely influence of the clerical family on these events.
Keywords: Roman Egypt; Ptolemaic Egypt; High priests of Ptah at Memphis